ANALISIS PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. JASER ABADI SENTOSA TIMIKA - Asridian Arif; RULAN L. MANDUAPESSY (CV. Adiba Aisha Amira, 2025)
This study aims to determine the eflect of motivation and work discipline on work productivity at PT Jaser Abadi Senrosa. The research method used in this study is the associative method used to find the relationship between certain variables. The data collected in this study are quantitative data and qualitative data sourced from PT Jaser Abadi Sentosa which are used as respondents using observation and questionnaire techniques. The analysis tool used in this study is SEM PLS. The results of the analysis show that work motivation does not have a significant eflect on employee work productivity and work discipline has a significant eflect on employee work productivity.